2014
DOI: 10.4018/ijopcd.2014070102
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Teachers in K-12 Online Learning

Abstract: Like many K-12 online learning programs, the Illinois Virtual High School (IVHS) began by utilizing vendor content to populate its online courses. In its fourth year, the IVHS began a concerted effort to design more of its own online course content internals. The aim of this study was to examine the nature of the support needed and application of tools used by IVHS course developers. The data consisted of a two-part, web-based survey and telephone interviews that were analyzed using descriptive statistics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In five of the six cases studied there was an onsite assistant with the remote students. This person was observed doing various tasks such as classroom management, communicating with the teacher about students' progress, tutoring students, distributing resources, and handling the organization and logistics of the classroom on the other side of the screen, which matches what Borup and Drysdale () reported in their work on the role of the “other” in K‐12 online and blended courses The teachers interviewed were adamant about emphasizing the critical role this support person plays in the success of videoconferencing, confirming existing literature on the topic (Barbour & Adelstein, ; Barbour & Mulcahy, ; Bower et al ., ; de la Varre, Kane, & Irvin, ; Hedestig & Kaptelinin, ; White, Ramierz, Smith, & Plonowski, ). Teacher C noted that she had “a system where the assistant sends me student work every day,” and Teacher E commented that she “could not survive without the teaching assistant over there.…”
Section: Resultssupporting
confidence: 77%
“…In five of the six cases studied there was an onsite assistant with the remote students. This person was observed doing various tasks such as classroom management, communicating with the teacher about students' progress, tutoring students, distributing resources, and handling the organization and logistics of the classroom on the other side of the screen, which matches what Borup and Drysdale () reported in their work on the role of the “other” in K‐12 online and blended courses The teachers interviewed were adamant about emphasizing the critical role this support person plays in the success of videoconferencing, confirming existing literature on the topic (Barbour & Adelstein, ; Barbour & Mulcahy, ; Bower et al ., ; de la Varre, Kane, & Irvin, ; Hedestig & Kaptelinin, ; White, Ramierz, Smith, & Plonowski, ). Teacher C noted that she had “a system where the assistant sends me student work every day,” and Teacher E commented that she “could not survive without the teaching assistant over there.…”
Section: Resultssupporting
confidence: 77%
“…Business simulation games are a practical way of learning about business challenges and how to overcome those challenges in a risk-free environment. Previous literature and researchers have endorsed views that business simulation game motivation [23] can enhance critical experimental thinking and learning [19,24], time management [24], and teamwork and collaborative learning [19,23]. Vanevenhoven and Liguori [25], and Zhang [26] hold the view that entrepreneurial knowledge, skills, and activities are complicated not only at this critical time, but also in the natural environment.…”
Section: Business Simulation Games and Their Benefitsmentioning
confidence: 99%
“…For example, Easton (2003) indicated that virtual teachers needed more advanced skills in managing instructional activities and assessments, and stronger engagement skills because interactions with students are separated by both time and space. Recognising that virtual teaching requires additional professional development, the Government of Nova Scotia and the Nova Scotia Teachers Union even included a requirement for higher levels of professional development for virtual teachers than face-to-face teachers as a part of their collective agreement in that Canadian province (Barbour & Adelstein, 2013). The data in this study underscores many of these themes found in North America.…”
Section: Professional Developmentmentioning
confidence: 68%